Malaysia A Silent Voice in World Trade Organization Dispute Settlement: Some Legal Considerations for Future Involvement in Renewable Energy Disputes - Andersen, Henrik (Journal of Malaysian and Comparative Law, 2018)
In the World Trade Organization (WTO), disputes relevant to the market for equipments producing renewable energy such as solar panels, are increasing. Such cases can be important for Malaysia as one of the world’s leading producers of solar panels. The article examines Malaysia’s engagement in WTO disputes from a legal perspective and finds that Malaysia is only engaged to a limited extent in WTO disputes. This limitation can be a problem as WTO law is developed through the WTO Dispute Settlement System and the suggests claims that both disputing parties and third parties can have an impact on that development. In order to help shape WTO law related to renewable energy in a preferred direction, Malaysia should become more involved in WTO dispute settlement.